Risk of Secondary ACL Injury in Adolescents Prescribed Functional Bracing After ACL Reconstruction. Issue 11 (12th November 2019) - Perrone, Gabriel S.; Webster, Kate E.; Imbriaco, Chris; Portilla, Gabriela M.; Vairagade, Amishi; Murray, Martha M.; Kiapour, Ata M.
Background: There is a high incidence of a secondary anterior cruciate ligament (ACL) injury in unbraced adolescent athletes. Little is known about the effect of functional bracing with regard to the risk of secondary ACL injuries among adolescents. Hypothesis: Our primary hypothesis was that adolescents would have a high rate of secondary ACL injury even with brace use. A secondary hypothesis was that the reinjury rate with brace use would be lower than that of a historical control group of unbraced patients. Study Design: Case series; Level of evidence, 4. Methods: A group of 219 patients (age <20 years at surgery) who underwent ACL reconstruction and were prescribed postoperative functional bracing during cutting and pivoting sports for 2 years after surgery completed a survey regarding reinjury to either knee. Rates of knee injuries following ACL reconstruction were calculated and compared with those reported in a similar unbraced cohort. The effect of demographic and anatomic factors on risk of secondary ACL injuries was also investigated. Results: The overall follow-up rate was 65% (142/219) at a mean 5.6 years after surgery. In the braced cohort, the overall graft retear rate was 10%, with the highest retear rates observed in male patients 17 years of age and younger (18%). The overall contralateral ACL injury and combined (graft or contralateral ACL) secondary injury rates were 13% and 23%, respectively, with female patients younger than 18 years having the highest contralateral and combined injury rates (17% and 26%, respectively). Younger age (odds ratio [OR], 0.70; P = .021), family history of ACL injury (OR, 2.81; P = .015), and higher lateral tibial slope (OR, 1.25; P = .016) were associated with increased risk of secondary knee injury in the braced cohort. Compared with the unbraced cohort, the braced cohort had a lower overall graft retear rate ( P = .028), a lower graft retear rate in patients younger than 18 years ( P = .012), lower early graft retear rate (within the first year after surgery) ( P = .011), and lower early graft retear rate in subjects younger than 18 years ( P = .003). Conclusion: Postoperative use of functional bracing can result in reduced risk of graft retear and no change in contralateral injury rates. Clinicians may want to consider the use of postoperative functional bracing in adolescent patients.